1971
DOI: 10.3133/ofr71242
|View full text |Cite
|
Sign up to set email alerts
|

Geology and economic potential for chromite in the Zhob Valley ultramafic rock complex, Hindubagh, Quetta division, West Pakistan

Abstract: The ultramafic rocks making up the Zhob Valley igneous complex have yielded small amounts of metallurgical-grade chromite since the early part of the century. From 1968-1970 a cooperative study undertaken by the Geological Survey of Pakistan and the U. S. Geological Survey, under the auspices of the Government of Pakistan and the Agency for International Development, evaluated the chromite potential of the Zhob Valley area and provided data for effective exploration. The Jung Tor Ghar ultramafic rock mass, cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The best preserved series of subophiolitic metamorphic rocks is located at the north-western side of the Jang Tor Ghar massif (Fig. 2) metamorphic sequences showing inverted metamorphic gradients (Rossman et al, 1971a;Munir and Ahmad, 1985;Mahmood, 1994 andMahmood et al, 1995). The series starts at the contact with peridotite-mylonites and garnet-amphibolites and grades downwards into amphibolites and fine-grained epidote amphibolites or epidote-actinolite-schists with inter layering of calcite.…”
Section: Jang Tor Ghar Massif (Jtg)mentioning
confidence: 97%
See 1 more Smart Citation
“…The best preserved series of subophiolitic metamorphic rocks is located at the north-western side of the Jang Tor Ghar massif (Fig. 2) metamorphic sequences showing inverted metamorphic gradients (Rossman et al, 1971a;Munir and Ahmad, 1985;Mahmood, 1994 andMahmood et al, 1995). The series starts at the contact with peridotite-mylonites and garnet-amphibolites and grades downwards into amphibolites and fine-grained epidote amphibolites or epidote-actinolite-schists with inter layering of calcite.…”
Section: Jang Tor Ghar Massif (Jtg)mentioning
confidence: 97%
“…More interest in detailed mapping and geological understanding of the area arose from its economic potential in high-grade chromite ore. Rossman et al (1971a) compiled preliminary maps of Muslim Bagh ophiolite. Rossman et al (1971b) also showed that the chromite deposits are located at the top of the dunite bodies which they called ''transgressive dunite''.…”
Section: Muslim Bagh Ophiolitementioning
confidence: 99%
“…It comprises of ultramafic rocks containing 80% of harzburgite and 20% of dunite; while the mafic deposits consist of gabbro with minor layers of serpentine. The ultramafic tectonites are comprised of <10% of dunite and >90% of the harzburgite [1,28].…”
Section: Malakand Agency-sakhakot (Dargai)mentioning
confidence: 99%
“…Rossman and Abbas [28] reported that the chromite in the upper part of the complex is found in 3-4.5m thick and 2km laterally extending layers, irregular massive bodies of <1m2 thickness in the western part while podiform, massive and irregular along the sharp contacts such as Hiru Shah deposit [1]. Main deposits are located at BarjoKanri, Hiru Shah, LandiKand, Qila and Badasar.…”
Section: Malakand Agency-sakhakot (Dargai)mentioning
confidence: 99%
“…The surrounding area comprises outcrops of mafic and ultra-mafic rocks of the Jang Tor massif of the Muslim Bagh Ophiolites, which are part of the Bela-Waziristan Ophiolite Belt. It marks the western margin of the Indian plate with the Afghan block of the Eurasian plate (Hunting Survey Corporation 1961; Rossman et al 1971;Khan et al 2007); and is thought to be a relic of the Neo-Tethyan ocean floor obducted onto the Indian plate subsequent to closure of the NeoTethys and collision of the Indian plate with the Eurasian plate at the Cretaceous-Tertiary boundary or later in the Palaeocene-Early Eocene times (Allemann 1979;Sarwar 1992;Ahmed 1996;Gnos et al 1996).…”
Section: Regional Geologymentioning
confidence: 99%